Insights into inflammatory priming of mesenchymal stromal cells: functional biological impacts - Najar, Mehdi; Krayem, Mohammad; Merimi, Makram; Burny, Arsène; Meuleman, Nathalie; Bron, Dominique; Raicevic, Gordana; Lagneaux, Laurence (Inflammation research, 2018)
Mesenchymal stromal cells (MSCs) are multipotent adult cells with relevant biological properties making them interesting tools for cell-based therapy. These cells have the ability to home to sites of injury and secrete bioactive factors as part of their therapeutic functions. However, depending on the local environment, diverse functions of MSCs can be modulated and thus can influence their therapeutic value. The specific cytokine milieu within the site of inflammation is vital in determining the fate and cell behaviors of MSCs. Indeed, inflammatory signals (called as inflammatory priming), may induce critical changes on the phenotype, multilineage potential, hematopoietic support and immunomodulatory capacity of MSCs. Thus, for appropriate clinical application of MSCs, it is important to well know and understand these effects. In summary, investigating MSC interactions with the inflammatory environment is necessary to empower the therapeutic value of MSCs.